Psychosocial factors and burnout syndrome in family physicians. Mexico - Aranda-Beltrán, Carolina (2005)
Objectives: To determine the presence of labor psychosocial factors (sociodemographic and labor factors) and their relationship with the burnout syndrome among family physicians. Materials and Methods: Two surveys were applied to family physicians who worked in two social security health institutions in the metropolitan area of Guadalajara, Mexico, in order to collect information on sociodemographic and labor variables and assess the presence of the syndrome with the Maslach Burnout Inventory Scale (MBI-HSS). Results: One hundred and ninety-seven physicians participated, 73 (37,1%) women and 124 (62,9%) men; 92,9% had medical specialization and the rest had bachelor’s degree but were considered family physicians according to their labor contract. The prevalence of burnout syndrome among family physicians was 41,8%. Both, the significant associations and sociodemographic and labor variables risk factors tended towards the “emotional exhaustion” dimension. Conclusions: Even that few variables were introduced in this study, those related to the development of the syndrome were important to be considered in a preventive level. We suggest that people with the syndrome signs and symptoms be derived for medical and/or psychological attention, and if required, give them incapacity benefit, with the purpose of improving the worker’s health and well-being as well as improving the social security worker’s life and attention quality.